PERAN KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA SUMBER DAYA MANUSIA DI WAWOTOBI - Abdul Hakim (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2015)
The purpose of this research was to examine the influence of leadership, organizationalculture, organizational commitment to the performance of human resources at the elementaryschool in Wawotobi. Data collection and issemination on the questionnaires respondents i.e.teacher of Civil Servants at the elementary school in Wawotobi.The sample of this researchsample as much as 77 primary school teachers who are scattered at 14 Elementary Schoolsin district Wawotobi who made the object of research. This research uses descriptive analysisto determine the characteristics of the respondents and the deskriptik of the respondents foreach of the indicator variable. The instrument used to test the relationships between variablesusing the SEM methods and analytical techniques PLS (Partial Least Square). The findingsof these research results showed the absence of significant positive influence of leadershipon organizational commitment. Leadership and organizational culture-positive significanteffect on performance of Human Resources, organizational culture positive significant effect oforganizational commitment, and organizational commitment affect positive signifikanterhadapHR performance. The implication that a good leader in the organization always providemotivation on subordinates, fostering creativity and innovation, as well as involving subordinatesin decision making, so that the performance of Human Resources will increase. The need for ahigh work discipline, morale and teamwork is good so that formed the organizational culture inimproving HR performanceKeywords: leadership, cultural organization, the commitment of organization, and performance